Leveraging the principles of lean six sigma in creating value for the user community - Shameem, Nilofar Maideen (Institutional Knowledge at Singapore Management University, 2017)
This is a case study on how Singapore Management University (SMU) Libraries used an evidence based approach to decision making, based on the principles of Lean Six Sigma. Academic Libraries and the services offered by them have been evolving over the years along with the changing landscape of higher education. By using a data-driven methodology, SMU Libraries, was able to provide a service that was relevant and tailored to the needs of its community.